(untitled) (Web of Teachers: Inderscience Research, 2025)
This article analyzes the significance of the master-apprentice tradition in Uzbek traditional singing, its role in the development of art, and its continuity. The master-apprentice system is regarded as a key means of preserving national cultural heritage and transmitting it to future generations. The article details how the master teaches technical skills to the apprentice, nurtures creativity, and conveys national values. Additionally, it explores how this tradition influences regional styles and its relevance in modern times. The article serves as an important theoretical basis for understanding and developing the rich heritage of traditional music art.